1976
DOI: 10.1002/ajh.2830010209
|View full text |Cite
|
Sign up to set email alerts
|

The human spleen as revealed by scanning electron microscopy

Abstract: The three-dimensional world of the spleen was explored by scanning electron microscopy on both arterially perfused and nonperfused specimens, as well as on plastic corrosion casts of splenic vasculatures. Of 25 spleens studied, 18 were examples of hypersplenism. These were contrasted to 7 essentially normal spleens taken from children being staged for treatment of Hodgkin's disease whose spleens proved to be uninvolved in the pathologic process. Splenic sinuses in all 25 spleens were typified by a degree of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…The spleen is divided into two main compartments: white pulp, which is abundant in T and B lymphocytes, and red pulp, which is abundant in red blood cells and macrophages (Barnhart and Lusher, 1976). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The spleen is divided into two main compartments: white pulp, which is abundant in T and B lymphocytes, and red pulp, which is abundant in red blood cells and macrophages (Barnhart and Lusher, 1976). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transillumination microscope observations of the spleen in living animals have lead to different results: open circulation was supported by MACKENZIE et al (1941) and PARPART et al (1955) but closed circulation by KNISELY (1936) andPECK andHOERR (1951) in spite of the same species used-the mouse and rat. Some studies using vascular casts of resin supported the opinion of open circulation in the organ (IRINO et al, 1977;FUJITA et al, 1985), whereas others suggested that closed circulation also occurred in mammalian spleens (BARNHART and BAECHLER, 1974;BARNHART and LUSHER, 1976;SCHMIDT et al, 1982). However, the technique of vascular casting with resin was criticized as unsuitable for proving a genuine closed circulation, i.e., the endothelial continuity between arterioles and sinuses (WEIss,1983).…”
mentioning
confidence: 99%
“…7,8 Pinocytotic vesicles, lysosomes, phagocytosed RBCs, and cellular debris are often present within the cytoplasm of LCs reflective of their phagocytic capabilities. 1,7,[9][10][11][12] Many of the prior observations concerning LCs have been made using electron microscopic and immunohistochemical staining, whereas the study of isolated purified cell populations has remained limited.…”
Section: Introductionmentioning
confidence: 99%